6 - Using ICTs for Social Justice in Africa - Firoze Manji (Africa Media Review, 2007)
This paper seeks to draw out the potentials of information and communications technologies (ICTs) for supporting the cause of social justice in Africa. The paper draws on Fahamu’s experiences of using ICTs for delivering distance learning programmes for human rights organisations using a mixture of CDROM, e-mail moderation and workshop-based learning. The potentials for delivering similar courses using handheld computers with built-in mobile phones are explored. The paper describes the development of Pambazuka News, a weekly electronic news and discussion forum for social justice that has grown in three years from a subscriber base of 300 to more than 70,000 each week. Pambazuka News has been used as an advocacy tool in a number of forums, notably at the first meeting of the Pan African Parliament and at AU meeting in Addis Ababa, Ethiopia, in July 2004, where it was the principal instrument for calling on African states to adopt the protocol for the rights of women in Africa. The paper discusses how SMS/text messaging from mobile phones has been used to enable people in Africa to sign online petitions. The paper argues that technology is a manifestation of social relations, reflecting the power and values of those who use it. It concludes that ICTs should not be left to those who want to make profits, but should be grasped as a powerful tool for social justice.